Rancang Bangun Sub-sistem Informasi untuk Pencatatan Transaksi di Program Studi Sistem Komputer Undip - Hermawan, Hermawan; Iman Satoto, Kodrat (Jurnal Sistem Komputer, 2011)
Currently in Computer Systems Engineering, Faculty of Engineering, Diponegoro University, Semarang, all records of financial transactions are still using Microsoft Excel and Microsoft Word. It can be assumed that to make a statement of financial performance is very difficult, both statements of cash receipts and cash disbursements report. It should be made a software for reporting financial performance can be monitored by the Head of Department and staff are entitled, at a moment's financial performance reports can be monitored and printed quickly, easily and accurately.This research is conducted by methods such as by literature study, system design and testing of the system. In the literature study used methods of research library of reference books related. The design of this study using a Rapid Application Development (RAD) so easy to develop applications. Applications are also made so easily accessible web-based and maintained (maintenance), because the application is placed on the server side. To secure information from unauthorized users, multi-user application created with the login system.The expected result is a sub-information systems for recording transactions and reporting financial performance can easily monitor and printed at any time needed.